Participation of municipal stakeholders in climate action planning in Zio 1 (Togo) and Zou (Benin) - Houndjo, Komlan; Kpotchou, Koffi (Edelweiss Applied Science and Technology, 2024)
Climate change has a local dimension and must be integrated into the development activities of local authorities. In the case of the municipalities of Zio1 (Togo) and Zou (Benin), the approach consisted of responding to climate issues at the local level. This local climate action planning exercise requires the participation of several local stakeholders in the municipality. The aim of this article is to examine the process of developing Sustainable Energy Access and Climate Action Plan (SEACAP) in Zio1 and Zou. The work is based on the hypothesis that the low level of participation of local stakeholders is a limitation in the planning of climate actions at local level. To verify this hypothesis, a survey was conducted among 449 people in the municipalities of Zio1 and Zou. The results show that municipal administrations, community leaders and civil society organizations were more involved in the process of setting up the SEACAP than state structures and economic stakeholders. Participation at grassroots population level remains very low. The SEACAP development process has limitations.